Culture And Leadership: The Case Of Romania - Raluca-Elena Hurduzeu (Romanian Economic Journal, 2015)
Globalization and internationalization lead to the development of a general image of good and effective leadership which influence the local leadership styles and the behavior of leaders. The latter must overcome the conflict between the desire to implement corporate standards which are internationally valid and the need to act locally in terms of organizational culture, business environment and leadership style. The knowledge of the national peculiarities and traditions, the understanding of their heritage and background, coming to grips with them are key-success factors for international co-operations and/or joint-ventures in today’s competitive world. The aim of this paper is to explore the connection between the organizational culture and the leadership style and aims to develop a better understanding of the Romanian leadership. It also provides important information and ideas on the leadership styles practiced in the companies within Romania. The study presents the research findings on the Romanian leadership style and connects it to the political, economic and cultural influences. As far as Romania is concerned, although the variations in the cultural configurations are of a great diversity and complexity, we may, however, identify two distinct types of organizational culture, supporting the hypothesis that these two categories are the extremes of a continuum with a wide variety of expression: a culture of ‘bureaucratic’ type, typical for: state-owned companies, former state firms in the post-privatisation period and the culture of ‘entrepreneurial’ type, in the process of formation, typical for the private companies formed after 1989. The most important problems that appear in the case of the multinational companies refer to the compensation values, sacred and taboo, the management of the gradual conflicts, etnocentrism, affiliation, faulty conciliation and naive realism. The leaders must learn to analyze the cultural differences and to identify those differences existing between the values, to recognize that there are different concepts of power and to avoid errors of reward.